COMPARATIVE STUDY ON DAMAGE OF POWER BATTERY BOX UNDER DIFFERENT VIBRATION SPECTRUMS - ZHAO Lihui; PAN Yu; FENG Jinzhi; ZHENG Songlin; ZHANG Dongdong (Jixie qiangdu)
Aiming at the vibration fatigue problem of the battery box of electric vehicles, based on the test loads in the real vehicle test field, the fatigue performance of the battery box was compared and analyzed based on single-axis and multi-axis (sequential loading, coupled loading) vibration loads. Firstly, the three-directional acceleration loads were collected at the sensitive points on the battery box in the test field. The power spectral densities were fitted and compared in the same direction of the loads at different measurement points respectively, and the power spectral densities were accelerated through the frequency-domain damage equivalence method to obtain the distribution characteristics of the random vibration three-directional acceleration power spectral densities under the test field specification. Secondly, based on the theory of random vibration fatigue analysis, the multi-axis sequential excitation and multi-axis coupled excitation of the battery box were constructed. Based on fatigue damage equivalence, a uniaxial strengthening spectrum excitation was constructed. Finally, the fatigue damage of the battery box under three kinds of excitation was compared and analyzed by the numerical simulation. The results show that the damage locations of the battery box are consistent under the three excitations. The damage under multi-axis coupled excitation is greater than that under multi-axis sequential excitation, and the single-axis enhancement spectrum has a better reproduction effect on the multi-axis coupled damage. This can provide guidance for conducting rapid vibration fatigue tests of battery boxes based on uniaxial enhanced load spectra.